Stochastic variance reduced gradient with hyper-gradient for non-convex large-scale learning - Yang, Zhuang (Applied intelligence (Dordrecht, Netherlands), 2023)
Non-convex optimization, which can better capture the problem structure, has received considerable attention in the applications of machine learning, image/signal processing, statistics, etc. With faster convergence rate, there have been tremendous studies on developing stochastic variance reduced algorithms to solve these non-convex optimization problems. However, as a crucial hyper-parameter for stochastic variance reduced algorithms, that how to select an appropriate step size is less researched in solving non-convex optimization problems. To address this gap, we propose a new class of stochastic variance reduced algorithms based on hyper-gradient, which has the ability to automatically obtain the online step size. Specifically, we focus on the variance-reduced stochastic optimization algorithms, the stochastic variance reduced gradient (SVRG) algorithm, which computes a full gradient periodically. We analyze theoretically the convergence of the proposed algorithm for non-convex optimization problems. Moreover, we show that the proposed algorithm enjoys the same complexities as state-of-the-art algorithms for solving non-convex problems in terms of finding an approximate stationary point. Thorough numerical results on empirical risk minimization with non-convex loss functions validate the efficacy of our method.